El carácter dialógico de la intervención y la investigación en trabajo social (2015)
ABSTRACT: Knowledge of current changes in the dimensions and dynamics of the social, is key to position the need to assume from the Social Work professional intervention based and contextualized. You need to turn at look at the way it has been conceived and exercised the intervention, through rigorous research from the ontological, epistemological, methodological and ethical-political social work as disciplinary field, enable it to assume the intervention as a category analysis, in which circumscribes the relationship between thought, action and transformation of social realities where you insert the work-professional knowledge.